2017
DOI: 10.1007/978-3-319-45596-9_204
|View full text |Cite
|
Sign up to set email alerts
|

Abstract: Factors Influencing the Unethical Behavior of Business People

Abstract: Corporate unethical behavior is nothing new. We are constantly bombarded with stories of managers engaging in illegal or unethical behavior. What is unknown are the reasons behind such behavior. Building upon Tenbrunsel and Messick's (1999) work on ethical framing we investigate the boundary conditions on how we look at ethical decisions. Through a qualitative and quantitative study, we propose that when managers are put into a business frame, they are more likely to solve problems without an ethical view an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Consider the importance that our participants placed on individual character traits as a cause of unethical behavior. Most studies on the causes of unethical behavior cite individual factors (Belle and Cantarelli, 2017;Boes et al, 2017;DuBois et al, 2013;Kornfeld, 2012;Sovacool, 2008). Often, these are described as classical character flaws: "greed, egocentrism, self-justification" (Belle and Cantarelli, 2017), or "a self-centered personality" (DuBois et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider the importance that our participants placed on individual character traits as a cause of unethical behavior. Most studies on the causes of unethical behavior cite individual factors (Belle and Cantarelli, 2017;Boes et al, 2017;DuBois et al, 2013;Kornfeld, 2012;Sovacool, 2008). Often, these are described as classical character flaws: "greed, egocentrism, self-justification" (Belle and Cantarelli, 2017), or "a self-centered personality" (DuBois et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The existing research on why people fail to act ethically identifies a range of contributors, including: pressure (Belle and Cantarelli, 2017;Davis et al, 2007: 200;Kornfeld, 2012;Sovacool, 2008), gain (Belle andCantarelli, 2017;Boes et al, 2017), mental/emotional state (Davis et al, 2007), character (Belle and Cantarelli, 2017;DuBois and Antes, 2018;Kornfeld, 2012;Ruiz-Palomino and Linuesa-Langreo, 2018;Sovacool, 2008), loss aversion (Belle and Cantarelli, 2017), health/ family trouble (Davis et al, 2007), relationships (Davis et al, 2007), competition (Boes et al, 2017), opportunity (Adams and Pimple, 2005), and cultural factors (Davis et al, 2007). These studies do not indicate which factors are most likely, only that they are factors in causing unethical behavior.…”
Section: Why People Fail To Act Ethicallymentioning
confidence: 99%
See 1 more Smart Citation
“…Sponsoring of major sporting contests and the competitive nature of winning may lead to unethical practices (Ionescu, 2015). Cooper and Frank (1991), as cited in Boes (2015), identify the following factors as influencing unethical behaviour: one's personal moral values and standards; family and friends who provide support and insight in relation to resolving ethical issues; leaders who pressurise employees to compromise ethical standards; an environment/culture that controls the pressure to compromise ethical values to achieve organisational goals; and an organisational leadership philosophy that emphasises ethics within operations. However, O'Fallon and Butterfield (2012) found that peer influence plays a major role in influencing ethical decision-making.…”
Section: Affiliationsmentioning
confidence: 99%
“…The more individuals observe their peers engaging in unethical behaviour, the more likely they are to engage in the same or similar activities. Boes (2015) states that if an individual believes that others are behaving unethically, http://dx.doi.org/10.18820/2519593X/pie.v38i1.12 then that individual will feel more inclined to behave unethically (like inverse peer pressure). Thus, there is a strong relationship between one's behaviour and one's expectation of others.…”
Section: Affiliationsmentioning
confidence: 99%